U.S. PERCEPTION AND POLICY ON SOUTH CHINA SEA PRE-COLD WAR: Received: 17th April 2024 Revised: 14th May 2024, 28th May 2024 & 30th May 2024 Accepted: 13th May 2024 - Liu Jinbo (PEOPLE: International Journal of Social Sciences, 2024)
After World War II, the United States’ South China Sea policy was formed based on its perception of the three before the Cold War. Through events such as France’s occupation of nine small islands, Japan’s occupation, and the struggle against Japan during the Pacific War, America has continuously deepened its cognition on the South China Sea and increasingly concerned its important value. With Japan’s successive retreats in the later stages of World War II, America gradually gained control of the Sea and took a dominant position in the regional dispute. With the continuous deepening of the United States’ appreciation and the changing of its identity, status, and the interests in this region, its policy has gradually taken shape